Swallowing disorders during and after treatment of larynx cancer - Zelic, Mirna; Petrovic Lazic, Mirjana; Pavlovic, Dragan (Medicinski časopis, 2021)
Dysphagia is a swallowing disorder that includes difficulty swallowing and controlling saliva as well as feeding difficulties. Dysphagia is a common symptom of laryngeal cancer, but also a consequence of surgical treatment as well as radiotherapy and chemotherapy of this neoplasma. Patients after total laryngectomy are at risk of developing malnutrition, aspiration pneumonia. Removal of anatomical structures and reorganization of remaining tissues has a significant impact on the physiology of swallowing. For most patients, safe swallowing is the main feature of a positive treatment outcome. Swallowing therapy is important before, during and after treatment of larynx cancer. The aim of this paper is to explore a correlation between swallowing disorders and laryngeal cancer treatment, and to understand the anatomical and physiological bases of dysphagia treatment.